Evaluation and Modeling of the Car Speed Control Process using a PID Controller - Barood, Faraj Ahmed Elzarook; Eshtaiwi, Abdulsalam (Yayasan Cita Cendekiawan Al Khwarizmi, 2021)
Car speed is an essential attribute for analysing the utility of a transport mode. The speed relationship between multiple modes of transport is of interest to traffic planners and operators. Nowadays, the cruise control system has become a common feature of modern cars. A car control system helps in providing comfortability to the driver while driving long-distance travel. Using a car control system, travelling on the highways has become easier than before because it reduces the mental and physical stress caused by regularly monitoring the speed of the car and frequently pressing the gas pedal to maintain the speed. This paper is aimed at modelling a car control system and examining its characteristics based on the PID control strategy. Proportional-Integral-Derivative (PID) controller provides a great way to stabilize systems. It has the ability to change the response of the system to be stable and reliable when it is used for controlling systems. This system is actualized with the help of MATLAB for simulation and control purposes. The paper showed that without the use of the PID controller, the speed was stable after 100 seconds, and when the controller was used and self-turned, the speed was approximately stable at 20 seconds, and this shows the effectiveness of using the PID controller.